Al-Isyârât al-Kauniyyah fi al-Hurûf al-Muqatha’ah Awâili al-Suwar ‘Inda Thanthawi Jauhari - Ilham Habibullah; Indri Wesdiarti Anggraini (Studia Quranika, 2017)
Muslim scholars have different views about the meaning and interpretation of the letters of muqatha'ah in the Qur'an. This issue also received special attention from the orientalists, as they saw that the letters of muqatha'ah belonged to the deficiency of the Qur'an. According to Thanthawi Jauhari the different views among Muslim scholars includes three points: First, the letters need not be interpreted. Second, the letters have related meaning to Asma Allah. Third, the letters are codes containing messages to read the Greatness of Allah in this universe. This paper discusses about the third point, which is exploring the meanings of the letters of muqhata'ah that related to this universe according to Thanthawi Jauhari.